Better Together: Evolution of Patient Stakeholder Engagement in Healthy Lifestyle Research After Acquired Brain Injury - Evan McShan; Audrey Self; Emily Nalepa; Simon Driver (Journal of Participatory Research Methods)
Engaging stakeholders in the conduction of research is increasingly recognized as beneficial and necessary in order to gain valuable insights. The following narrative describes the process of engaging and partnering with patient stakeholders in a six-year systematic line of research to modify an evidence-based healthy lifestyle program called the Diabetes Prevention Program Group Lifestyle Balance (DPP-GLB) for individuals with acquired brain injury (ABI), including traumatic brain injury (TBI) and cerebrovascular accident/stroke (CVA). We will describe how patient stakeholders were regularly engaged and encouraged to offer feedback to support study activities, including curriculum modification, research design, knowledge translation, and future research opportunities, to create a meaningful and patient-centered program for people with ABI. Commentary from two patient stakeholders who have been part of the modification, implementation, and dissemination of both programs is also included. Additionally, the importance of including patient stakeholders in all stages of research and future directions of the modified programs are discussed from the perspective of our research team.